The Effects of Milling Strategies on Forces, Material Removal Rate, Tool Deflection, and Surface Errors for the Rough Machining of Complex Surfaces - Bagci, Eyup; Yuncuoglu, Ercument U. (ASSOC MECHANICAL ENGINEERS TECHNICIANS SLOVENIA, 2017)
The high-performance machining of curved surfaces is a highly critical process that is crucial in modern engineering applications. Different methodologies and CAM tools have been developed by manufacturers to improve the efficiency of the sculptured surface milling. The determination of appropriate tool path strategies and milling conditions is crucial in ensuring a high productivity rate, meeting the better surface texture values, and lower cutting forces, tool deflection, and surface errors. The objective of this research is to analyse the effect of tool path strategies on dynamic tool deflection, cutting forces, machining time, effective cutter diameter (ECD), cutter/workpiece engagement (CWE) area, instantaneous material removal rate (IMRR), and machining errors in rough machining of a sculptured surface. The B-rep solid modeling-based simulation and the optimization system were developed and integrated with the commercial CAD/CAM software for 3-axis ball-end milling. The experimental results clearly show the influence of the cutter path strategies on machining times and their importance for reducing time needed and, consequently, costs. It was observed that the profiles of deflection, IMRR values, cutting forces, machining errors and ECD values match very well for cutting strategies. Machining strategies employed include various degrees of zig-zag, profiling, and spiral. The conclusion is that the 90 degrees zig-zag strategy provokes the lowest cutting forces, tool deflection, and surface error values. The in-house NC simulation system performed well in determining values and the location of milling form errors on the surface.
Keywords: milling; free-form surfaces; MRR; machining errors; cutting strategies; PATH STRATEGIES; SCULPTURED SURFACE; FREEFORM SURFACE; CUTTING FORCES; SIMULATION; STEEL; GEOMETRIES; SELECTION; DIRECTION; LIFE; Engineering